Comparative Analysis of Amorphous and Biodegradable Copolymers: A Molecular Dynamics Study Using a Multi-Technique Approach - Alovidin Nazirov; Jacek Klinowski; John Nobleman (Molecules)
We investigate the molecular dynamics of glycolide/lactide/caprolactone (Gly/Lac/Cap) copolymers using differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), 1H second-moment, 1H spin-lattice relaxation time (T1) analysis, and 13C solid-state NMR over a temperature range of 100–413 K. Activation energies and correlation times of the biopolymer chains were determined. At low temperatures, relaxation is governed by the anisotropic threefold reorientation of methyl (-CH3) groups in lactide. A notable change in T1 at ~270 K and 294 K suggests a transition in amorphous phase mobility due to translational diffusion, while a second relaxation minimum (222–312 K) is linked to CH2 group dynamics influenced by caprolactone. The activation energy increases from 5.9 kJ/mol (methyl motion) to 22–33 kJ/mol (segmental motion) as the caprolactone content rises, enhancing the molecular mobility. Conversely, lactide restricts motion by limiting rotational freedom, thereby slowing global dynamics. DSC confirms that increasing ε-caprolactone lowers the glass transition temperature, whereas higher glycolide and lactide content raises it. The onset temperature of main-chain molecular motion varies with the composition, with greater ε-caprolactone content enhancing flexibility. These findings highlight the role of composition in tuning relaxation behavior and molecular mobility in copolymers.